Game Development on Dap Based Physical Education Study (Developmentally Appropriate Practice) for Basic School Children - Ruben Pardamean Hutapea; Nurhayati Simatupang; Indra Kasih (Budapest International Research and Critics University, 2021)
This study aims to develop games in physical education subjects in schools based on DAP (Developmentally Appropriate Practice). Then in this research will produce a product in the form of a game module with the concept of DAP (Developmentally Appropriate Practice) for basic locomotor motion. This type of research is development research based on the Borg and Gall Model. The trial subjects consisted of material experts, game experts, and Physical Education teachers at Imanuel Medan and Methodist 1 Medan elementary schools. The first stage of this model is the needs research stage, followed by the design stage and the third stage is development and implementation. In this stage all stages involve an evaluation and revision process. Material expert judgment is 89%, for game experts by 90.8% and the results of the sports teacher assessment at stage I was 73.8% and at stage II was 86%. Results The results of product appraisal have increased with a difference of significance of 12.2%. This shows that the product developed on locomotor motion through game development based on DAP (Developmentally Appropriate Practice) is appropriate for use in the implementation of learning.